An Assessment of Timeliness and Quality of Communicable Disease Surveillance System in the Kurdistan Region of Iraq - Soran Amin Hamalaw MPH; Ali Hattem Bayati PhD; Muhammed Babakir-Mina PhD (SAGE Publishing, 2021)
Background The quality of the surveillance system can be defined by attributes such as completeness, timeliness, usefulness, simplicity, flexibility, acceptability, and reliability. This study aims to assess these quality features of the communicable disease surveillance system (CDSS) in the Kurdistan Region of Iraq. Methods This study was conducted using a retrospective review of records and documents, and the interviews with the surveillance staff (n = 82) of the Kurdistan governorates during 2018, 2019, and 2020. The World Health Organization (WHO) guideline 2006 indicators were used for evaluation and monitoring the quality of the communicable disease surveillance system. The data analyzed and showed as frequencies and percentages using Statistical Package for the Social Sciences (SPSS) version 26 software. Results The reporting timeliness declined from 98% in 2019 to 69% in 2020. At the same time, there was an improvement in completeness of reporting from 83% in 2018 to 99% in 2020. The total scores of other surveillance quality attributes, simplicity, usefulness, flexibility, acceptability, and reliability, were 75%, 72%, 67%, 72%, and 69%, respectively. Conclusion Current findings demonstrate that the CDSS is still facing significant challenges in timeliness simplicity, usefulness, flexibility, acceptability, and reliability. Further studies to assess the system's quality, particularly the system's timeliness of outbreak response, sensitivity, and specificity, are recommended.